Applying a learning design methodology in the flipped classroom approach – empowering teachers to reflect and design for learning - Evangelia Triantafyllou (Læring og Medier, 2016)
One of the recent developments in teaching that heavily relies on current technology is the “flipped classroom” approach. In a flipped classroom the traditional lecture and homework sessions are inverted. Students are provided with online material in order to gain necessary knowledge before class, while class time is devoted to clarifications and application of this knowledge. The hypothesis is that there could be deep and creative discussions when teacher and students physically meet. This paper discusses how the learning design methodology can be applied to represent, share and guide educators through flipped classroom designs. In order to discuss the opportunities arising by this approach, the different components of the Learning Design – Conceptual Map (LD-CM) are presented and examined in the context of the flipped classroom. It is shown that viewing the flipped classroom through the lens of learning design can promote the use of theories and methods to evaluate its effect on the achievement of learning objectives, and that it may draw attention to the employment of methods to gather learner responses. Moreover, a learning design approach can enforce the detailed description of activities, tools and resources used in specific flipped classroom models, and it can make educators more aware of the decisions that have to be taken and people who have to be involved when designing a flipped classroom. By using the LD-CM, this paper also draws attention to the importance of characteristics and values of different stakeholders (i.e. institutions, educators, learners, and external agents), which influence the design and success of flipped classrooms. Moreover, it looks at the teaching cycle from a flipped instruction model perspective and adjusts it to cater for the reflection loops educators are involved when designing, implementing and re-designing a flipped classroom. Finally, it highlights the effect of learning design on the guidance, representation and sharing of flipped designs and how such an effect can move forward research on the flipped classroom.